High resolution profiling of cell cycle-dependent protein and phosphorylation abundance changes in non-transformed cells - Camilla Rega; Ifigenia Tsitsa; Theodoros I. Roumeliotis; Izabella Krystkowiak; Maria Portillo; Lu Yu; Julia Vorhauser; Jonathon Pines; Jörg Mansfeld; Jyoti Choudhary; Norman E. Davey (Nature Communications)
Abstract The cell cycle governs a precise series of molecular events, regulated by coordinated changes in protein and phosphorylation abundance, that culminates in the generation of two daughter cells. Here, we present a proteomic and phosphoproteomic analysis of the human cell cycle in hTERT-RPE-1 cells using deep quantitative mass spectrometry by isobaric labelling. By analysing non-transformed cells and improving the temporal resolution and coverage of key cell cycle regulators, we present a dataset of cell cycle-dependent protein and phosphorylation site oscillation that offers a foundational reference for investigating cell cycle regulation. These data reveal regulatory intricacies including proteins and phosphorylation sites exhibiting cell cycle-dependent oscillation, and proteins targeted for degradation during mitotic exit. Integrated with complementary resources, our data link cycle-dependent abundance dynamics to functional changes and are accessible through the Cell Cycle database (CCdb), an interactive web-based resource for the cell cycle community.